Basis Data Relasional dalam Kreasi Organisasi File Akuntansi (Suatu Bahasan atas Pendekatan Penyajian Informasi Akuntansi Perusahaan Berbasis Komputer) - Idris Asmuni; Rangga Firdaus (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2005)
The Integrated approach of DataBase Management Systems (DBMS) has significant impact to the way ofaccounting information report, mainly in the subject to change data into communication which is easilyunderstandable. The audit software is basically designed according to the way of database modelling systems.This paper attempts to explain the creation of relational database theoretically and any other aspects ofdatabase use it self. The aims of database application have contributed various items to the management report.The transaction processing cycle supplies the framework what has to be fullfilled in the needs of accountinginformation, therefore database itself is oriented to the transaction processing cycle.The Relational database approach actually has the same idea with other activities which affected generalform of database itself. The accounting systems however is one field of conceptual framework in building themanagement report in monetary units. Therefore, it will be suggested to the accountant and systems informationanalysts to pay attention more for the essence of modelling accounting database.Keywords: modelling accounting database, Database Management Systems (DBMS), audit software.